Resin-based heat-proof composite material coated with low-temperature curing high-temperature infrared stealth coating on surface and preparation method of resin-based heat-proof composite material
By coating the high-temperature infrared stealth coating composed of low-emissivity filler and glass-phase organic resin on the surface of the resin-based heat-proof composite material, and adopting a low-temperature curing process, the problem of the coating falling off in a high-temperature environment is solved, and wide temperature is achieved The low infrared emissivity and bonding performance of the high temperature zone maintain the infrared stealth function of the aircraft.
Patent Information
- Application Number
- CN202510058754.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The problems of the fall off and peeling of the infrared stealth coating of existing resin-based heat-proof composite materials in high temperature environments have led to the damage to the infrared stealth function of the aircraft.
High-temperature infrared stealth coating composed of low emissivity filler and bonded phase. The low emissivity filler consists of nano silver powder or nano silver palladium powder and sheet aluminum powder. The bonded phase consists of glass phase and organic resin, and passes through low temperature. The curing process carries out the coating.
The bonding performance of the wide temperature domain low infrared emissivity and high temperature zone is achieved, avoiding the shedding and peeling of the coating in a high temperature environment, and maintaining the infrared stealth function of the aircraft.
Smart Images

Figure CN119505647A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-temperature infrared stealth resin-based composite materials, and in particular to a resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating and a preparation method thereof. Background Art
[0002] When a high-speed aircraft is flying at high speed, the air around the aircraft is strongly compressed and subjected to intense friction. Most of the aircraft's kinetic energy is converted into heat energy, causing the air temperature around the aircraft to rise sharply, forming an aerodynamic heating flow field with high temperature, high pressure and high heat flow. Therefore, the thermal protection problem is one of the key issues that high-speed aircraft must solve. On the other hand, aerodynamic heating causes the surface of the aircraft to have a higher temperature, and the infrared exposure characteristics are prominent, making the aircraft seriously threatened by infrared detection and guidance weapons and equipment. The infrared stealth problem is another key issue that high-speed aircraft must solve.
[0003] Resin-based heat-resistant composite materials are a type of composite material that is widely used in thermal protection systems of high-speed aircraft. On the one hand, resin-based heat-resistant composite materials can remove a large amount of heat through decomposition and carbonization in a thermal environment, thus playing a role in heat insulation; on the other hand, high-temperature infrared stealth coatings can be applied to the surface of resin-based heat-resistant composite materials to significantly reduce infrared radiation characteristics and play a role in infrared stealth. The following conditions must be met when coating resin-based heat-resistant composite materials with high-temperature infrared stealth coatings: First, the infrared stealth coating has a low emissivity over a wide temperature range, and can still firmly adhere to the surface of the material without falling off when the composite material decomposes at high temperature; second, the construction process is simple, and it must have low cost and low energy consumption characteristics; third, the high-temperature infrared stealth coating must have the characteristics of low-temperature curing to prevent the decomposition of the resin-based heat-resistant composite material caused by high-temperature treatment. Chinese patent publication number CN112920442A discloses a resin-based heat-proof composite material with a high-temperature infrared stealth coating on its surface and a preparation method thereof. The resin-based heat-proof composite material with a high-temperature infrared stealth coating on its surface is dried and cured at 120-150°C, which causes excessive damage to some resin-based composite material systems. After a thermal shock test at 800°C for 10 minutes, the prepared resin-based heat-proof composite material with a high-temperature infrared stealth coating on its surface has basically no obvious cracking, shedding and other phenomena, and the infrared emissivity of the coating has not changed significantly after the test. However, it can be seen from the photos of the coating after the test that a small amount of shedding occurs in the coating after the test, and the high-temperature bonding between the coating and the resin-based heat-proof composite material needs to be further improved. Summary of the invention
[0004] In view of the above shortcomings, the present invention provides a resin-based heat-resistant composite material with a surface coated with a low-temperature cured high-temperature infrared stealth coating and a preparation method thereof. The composite material has the advantages of low infrared emissivity in a wide temperature range, high bonding performance between the coating and the substrate in a wide temperature range, and excellent high temperature resistance. The specific technical scheme is as follows: A resin-based heat-proof composite material with a low-temperature-cured high-temperature infrared stealth coating coated on its surface, comprising, from the inside to the outside, a resin-based heat-proof composite material and a high-temperature infrared stealth coating, wherein the high-temperature infrared stealth coating is composed of a low-emissivity filler and a bonding phase, wherein the low-emissivity filler is a mixed filler composed of nano silver powder or nano silver palladium powder and flaky aluminum powder, and the bonding phase is composed of a glass phase and an organic resin.
[0005] Preferably, in the above-mentioned resin-based heat-resistant composite material with a low-temperature cured high-temperature infrared stealth coating coated on the surface, the mass fraction of the low-emissivity filler in the coating is 80%~95%, the mass fraction of nanosilver or nanosilver palladium powder in the mixed filler is 10%~90%, and the mass fraction of flaky aluminum powder is 10%~90%; the mass fraction of palladium in the nanosilver palladium powder is 5%~30%, and the mass fraction of nanosilver is 70%~95%; the particle size of the nanosilver and palladium powder is 30nm~150nm, and the particle size of the flaky aluminum powder is 5μm~40μm.
[0006] Preferably, in the resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating, the mass content of the organic resin in the bonding phase is 5% to 10%, and the mass content of the glass phase is 90 to 95%, and the organic resin is one of epoxy resin, acrylic resin, epoxy-modified silicone resin, and fluororesin; the glass phase is lead-containing low-melting-point glass, the main component of which is PbO-B 2 O 3 , where the mass fraction of PbO is 1%~30%, B 2 O 3 The mass fraction is 20%~80%, and the softening point temperature is 350℃~400℃. Adding organic resin to the binder phase is conducive to low-temperature curing, achieving low infrared emissivity, and improving the bonding between the coating and the substrate; the content of organic resin needs to be controlled within a certain range. Too high an organic resin content will affect the infrared stealth performance, and will severely decompose during high-temperature use, causing the coating to fall off. Too low an organic resin content will affect the coating film formation.
[0007] Preferably, in the resin-based heat-resistant composite material with a surface coated with a low-temperature cured high-temperature infrared stealth coating, the resin-based heat-resistant composite material reinforcement is one of carbon fiber, glass fiber, high-silica fiber, aramid fiber, and quartz fiber, and the resin matrix is one of epoxy resin, phenolic resin, benzoxazine resin, aromatic acetylene resin, and silicon aromatic acetylene resin; the braiding form of the reinforcement is one of three-dimensional five-directional fabric, 2.5D fabric, stitched fabric, and needle-punched fabric; the density of the resin-based heat-resistant composite material is 0.5g / cm 3 ~1.5g / cm 3 .
[0008] Preferably, in the above-mentioned resin-based heat-resistant composite material whose surface is coated with a low-temperature-cured high-temperature infrared stealth coating, the thickness of the high-temperature infrared stealth coating is 10 μm to 200 μm.
[0009] A method for preparing the above-mentioned resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating comprises the following steps: (1) Preparation of resin-based heat-resistant composite materials; (2) Grinding and roughening the coating surface of the resin-based heat-resistant composite material to be coated; (3) The high-temperature infrared stealth coating is applied to the surface of the resin-based heat-resistant composite material by brushing or room-temperature spraying, and then subjected to low-temperature curing and polishing. The low-temperature curing process parameters are: temperature of 70°C to 100°C and time of 1h to 2h to obtain a high-temperature infrared stealth coating.
[0010] Preferably, in the above-mentioned preparation method, the step (1) comprises cleaning the mold, applying a mold release agent on the mold surface, and completing mold treatment; assembling the resin-based composite material fabric with the mold and performing an air tightness inspection; injecting liquid resin into the closed mold cavity under pressure to complete the infiltration of the resin-based composite material fabric, and obtaining the resin-based heat-resistant composite material through heating, curing, and demolding.
[0011] Preferably, in the above-mentioned preparation method, the infiltration pressure is 0.2MPa~1.2MPa; the viscosity of the liquid resin is 20mPa·s~600mPa·s; the heating and curing temperature is 50°C~280°C, and the curing time is 2h~40h.
[0012] Preferably, in the above-mentioned preparation method, the high-temperature infrared stealth coating is mainly composed of a low-emissivity filler, a binder and an organic carrier; the binder is composed of glass powder and an organic resin. The high-temperature infrared stealth coating is prepared by the following method: the glass powder after melting, water cooling and ball milling is passed through a 200-400 mesh sieve, and then the glass powder and the low-emissivity filler are mixed evenly with a planetary gravity mixer, and then mixed evenly with the organic resin and the organic carrier, and then ground with a three-roll grinder to obtain the high-temperature infrared stealth coating.
[0013] Preferably, in the above-mentioned preparation method, the organic carrier is mainly composed of 70% to 80% butyl carbitol, 8% to 12% tributyl citrate, 2% to 5% ethyl cellulose, 2% to 5% Span-85 and 3% to 6% 1,4-butyrolactone in a mass fraction, and the mass fraction of the organic carrier in the high-temperature infrared stealth coating is 5% to 25%.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The resin-based heat-resistant composite material with a high-temperature infrared stealth coating on the surface of the present invention adopts a high-temperature infrared stealth coating system with a mixed powder of nano-metal and flaky metal with low emissivity as filler, and an organic resin with low-temperature curing characteristics and a low-melting-point glass as a bonding phase. The flaky metal powder in the coating has good coverage and can be quickly cured into a film at low temperature to achieve low emissivity; in addition, the nano-scale metal powder in the coating has high sintering activity and can be quickly sintered in a high-temperature environment. It also has low emissivity characteristics at high temperatures, thereby achieving low emissivity in a wide temperature range, solving the stealth problem of aircraft in a wide temperature range.
[0015] 2. The high-temperature infrared stealth coating of the present invention uses organic resin and low-melting-point glass as a mixed bonding phase. The organic resin in the coating is responsible for bonding the low-emissivity filler in the low-temperature zone, so that the coating adheres to the surface of the composite material; under high-temperature use environment, the organic resin decomposes and the glass phase can melt quickly, and together with the sintering characteristics of the metal powder, it provides bonding in the high-temperature zone, so that the low-emissivity filler can be firmly attached to the surface of the resin-based composite material, avoiding the shedding and peeling of the high-temperature infrared stealth coating due to the decomposition of the composite material under the use environment, thereby maintaining the infrared stealth function of the aircraft.
[0016] 3. The composite material preparation method of the present invention adopts a low-temperature curing process, which has low energy consumption and reduces damage to the resin-based heat-resistant composite material.
[0017] 4. The present invention adopts a relatively simple coating process, the process and equipment are simple, large components can be prepared, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a photo of the resin-based heat-resistant composite material after grinding and roughening treatment in Example 1 of the present invention.
[0020] Figure 2 This is a photo of the high-temperature infrared stealth coating prepared in Example 1 of the present invention.
[0021] Figure 3 These are photos of the resin-based heat-resistant composite material with a high-temperature infrared stealth coating on its surface in Example 1 of the present invention after undergoing thermal tests at 600°C-10min and 1000°C-10min.
[0022] Figure 4This is a photograph of the resin-based heat-resistant composite material with a high-temperature infrared stealth coating on its surface after being subjected to a quartz lamp thermal test in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc. can be purchased from the market or can be prepared by existing methods.
[0024] Example 1 A resin-based heat-proof composite material with a low-temperature curing high-temperature infrared stealth coating on the surface, which is composed of a resin-based heat-proof composite material and a high-temperature infrared stealth coating from the inside to the outside. The resin-based heat-proof composite material uses quartz fiber as a reinforcement and phenolic resin as a resin matrix. The reinforcement is woven in a 2.5D fabric. The density of the resin-based heat-proof composite material is 0.65g / cm 3 The high-temperature infrared stealth coating is composed of a low-emissivity filler and a binder phase. The low-emissivity filler in the high-temperature infrared stealth coating has a mass fraction of 90%, which is composed of a mixed filler of 56% nano silver powder and 44% flaky aluminum powder. The particle size of the nano silver is 50nm and the particle size of the flaky aluminum powder is 30μm. The binder phase is composed of 90% PbO-B 2 O 3 The glass phase and the mass fraction of 10% bisphenol A epoxy resin are composed of PbO-B 2 O 3 The mass fraction of PbO in the glass phase is 21%, and the mass fraction of B 2 O 3 The mass fraction is 79%, the glass softening point is 350°C, and the thickness of the high-temperature infrared stealth coating is 100μm.
[0025] This embodiment also provides a method for preparing a resin-based heat-resistant composite material with a high-temperature infrared stealth coating on its surface, comprising the following steps: (1) Clean the mold, apply release agent on the mold surface, and complete the mold processing; (2) Assemble the resin-based composite fabric and the mold and perform an air tightness inspection; (3) Using a pressure of 0.4 MPa, a liquid phenolic resin with a viscosity of 50 mPa·s was injected into the closed mold cavity to complete the impregnation of the resin-based composite fabric, and then heated and cured at 80°C for 36 h. After that, the mold was removed to complete the preparation of the resin-based heat-resistant composite material. (4) The surface of the resin-based heat-resistant composite material to be coated is subjected to grinding and roughening treatment. The resin-based heat-resistant composite material after grinding and roughening treatment is as follows: Figure 1 As shown; (5) The high-temperature infrared stealth coating is applied to the surface of the resin-based heat-resistant composite material by a brush coating process, and then cured at 70°C for 2 h and polished to complete the preparation of the high-temperature infrared stealth coating (see Figure 2 ).
[0026] Wherein, in step (5), the high-temperature infrared stealth coating is prepared by the following method: the glass powder after melting and ball milling is passed through a 200-400 mesh sieve, and then the glass powder, nano silver powder, and flaky aluminum powder are mixed evenly, and finally mixed evenly with bisphenol A epoxy resin and an organic carrier and ground to obtain the high-temperature infrared stealth coating. The organic carrier in the high-temperature infrared stealth coating is mainly composed of 80% by mass of butyl carbitol, 10% tributyl citrate, 3% ethyl cellulose, 3% Span-85 and 4% 1,4-butyrolactone, and the mass fraction of the organic carrier in the high-temperature infrared stealth coating is 20%.
[0027] The high-temperature infrared stealth coating prepared in this embodiment has good adhesion to the surface of the resin-based heat-resistant composite material. The coating adhesion test is carried out with reference to the standard GB9286-1998. After gluing, the coating has no peeling, which is level 0 and the adhesion is qualified. Figure 3 The photos of the resin-based heat-resistant composite material with high-temperature infrared stealth coating on the surface after 600℃-10min and 1000℃-10min thermal tests. Figure 4 The following are photos of the resin-based heat-resistant composite material coated with a high-temperature infrared stealth coating after being tested by a quartz lamp. The photos show that the high-temperature infrared stealth coating is intact without cracking or peeling. The original state of the coating (before the test), after a 600℃ heat test, after a 1000℃ heat test, and after a quartz lamp test (the highest heat flux is 150kW / m 2 , test time 600s) are 3~5μm room temperature infrared emissivity are 0.23, 0.10, 0.13 and 0.13 respectively. The infrared emissivity of the high-temperature infrared stealth coating is significantly reduced after the thermal test, indicating that the high-temperature infrared stealth coating prepared on the surface of the resin-based heat-resistant composite material exhibits low emissivity characteristics in a wide temperature range, excellent heat resistance, and strong high-temperature bonding with the substrate.
[0028] Comparative Example 1 The difference between this comparative example and Example 1 is that the low emissivity filler is nano silver powder, and the particle size of the nano silver is 50 nm; the other components and preparation method are the same as those in Example 1.
[0029] The coating prepared in this comparative example has good bonding with the surface of the resin-based heat-resistant composite material. After gluing, the coating has no peeling and is grade 0, and the adhesion is qualified. The 3~5μm normal temperature infrared emissivity of the coating in the original state (before assessment), after 600℃ heat assessment, after 1000℃ heat assessment, and after quartz lamp assessment are 0.29, 0.20, 0.16, and 0.15, respectively.
[0030] Comparative Example 2 The difference between this comparative example and Example 1 is that the bonding phase is PbO-B 2 O 3 Glass phase, without adding bisphenol A epoxy resin; other components and preparation method are the same as Example 1.
[0031] In the process of preparing the coating in this comparative example, after curing at 70°C for 2h in step (5), the high-temperature infrared stealth coating and the resin-based heat-resistant composite material were poorly bonded, and the coating peeled off after gluing, which was level 3, and the adhesion was unqualified. The 3~5μm normal temperature infrared emissivity of the coating prepared in this comparative example in the original state (before assessment), after 600°C heat assessment, after 1000°C heat assessment, and after quartz lamp assessment were 0.38, 0.23, 0.25, and 0.24, respectively.
[0032] Comparative Example 3 The difference between this comparative example and Example 1 is that the binder phase is composed of 85% by mass of PbO-B 2 O 3 The glass phase and the mass fraction of bisphenol A epoxy resin are 18%; other component parameters and preparation methods are the same as those in Example 1.
[0033] In the process of preparing the coating of this comparative example, the high-temperature infrared stealth coating and the resin-based heat-resistant composite material are well bonded after curing at 70°C for 2h in step (5). The coating has no peeling after gluing, which is level 0, and the adhesion is qualified. The 3~5μm normal temperature infrared emissivity of the coating in the original state (before assessment), after 600°C heat assessment, after 1000°C heat assessment, and after quartz lamp assessment are 0.24, 0.30, 0.39, and 0.37, respectively. After 600°C assessment and 1000°C assessment, a small part of the coating falls off.
[0034] Example 2 A resin-based heat-resistant composite material with a low-temperature curing high-temperature infrared stealth coating on the surface, which is composed of a resin-based heat-resistant composite material and a high-temperature infrared stealth coating from the inside to the outside. The resin-based heat-resistant composite material uses glass fiber as a reinforcement and benzoxazine resin as a resin matrix. The reinforcement is woven in a sutured fabric. The density of the resin-based heat-resistant composite material is 1.50 g / cm 3The high-temperature infrared stealth coating is composed of a low-emissivity filler and a binder phase. The mass fraction of the low-emissivity filler in the high-temperature infrared stealth coating is 85%, which is composed of a mixed filler of 45% nano silver powder and 55% flaky aluminum powder. The particle size of the nano silver is 60nm and the particle size of the flaky aluminum powder is 40μm. The binder phase is composed of 92% PbO-B 2 O 3 The glass phase and 8% bisphenol A epoxy resin by mass fraction are composed of PbO-B 2 O 3 The mass fraction of PbO in the glass phase is 28%, 2 O 3 The mass fraction is 72%, the glass softening point is 350°C, and the thickness of the high-temperature infrared stealth coating is 80μm.
[0035] This embodiment also provides a method for preparing a resin-based heat-resistant composite material with a high-temperature infrared stealth coating on its surface, comprising the following steps: (1) Clean the mold, apply release agent on the mold surface, and complete the mold processing; (2) Assemble the resin-based composite fabric and the mold and perform an air tightness inspection; (3) Using a pressure of 0.6 MPa, a liquid benzoxazine resin with a viscosity of 50 mPa·s was injected into the closed mold cavity to complete the infiltration of the resin-based composite fabric, and then heated and cured at 200 °C for 5 h. After that, the mold was removed to complete the preparation of the resin-based heat-resistant composite material. (4) Grinding and roughening the coating surface of the resin-based heat-resistant composite material to be coated; (5) The high-temperature infrared stealth coating is applied to the surface of the resin-based heat-resistant composite material by a brush coating process, and then cured at 90°C for 2 h and polished to complete the preparation of the high-temperature infrared stealth coating.
[0036] Wherein, in step (5), the high-temperature infrared stealth coating is prepared by the following method: the glass powder after melting and ball milling is passed through a 200-400 mesh sieve, and then the glass powder, nano silver powder, and flaky aluminum powder are mixed evenly, and finally mixed evenly with bisphenol A epoxy resin and an organic carrier and ground to obtain the high-temperature infrared stealth coating. The organic carrier in the high-temperature infrared stealth coating is mainly composed of 75% by mass of butyl carbitol, 10% tributyl citrate, 5% ethyl cellulose, 5% Span-85 and 5% 1,4-butyrolactone, and the mass fraction of the organic carrier in the high-temperature infrared stealth coating is 20%.
[0037] The high-temperature infrared stealth coating prepared in this embodiment has good adhesion with the surface of the resin-based heat-resistant composite material. After gluing, the coating has no peeling and is grade 0, and the adhesion is qualified. The resin-based heat-resistant composite material coated with the high-temperature infrared stealth coating on the surface has been subjected to 600℃-10min, 1000℃-10min thermal tests, quartz lamp thermal tests (maximum heat flux 150kW / m 2 , the high-temperature infrared stealth coating is intact without cracking or falling off after the test time of 600s. The measured 3~5μm normal temperature infrared emissivity of the coating in the original state (before the test), after the 600℃ heat test, after the 1000℃ heat test, and after the quartz lamp test are 0.25, 0.13, 0.15, and 0.15, respectively. The infrared emissivity of the high-temperature infrared stealth coating is significantly reduced after the heat test, indicating that the high-temperature infrared stealth coating prepared on the surface of the resin-based heat-resistant composite material exhibits low emissivity characteristics in a wide temperature range, excellent heat resistance, and strong high-temperature bonding with the substrate.
[0038] Example 3 A resin-based heat-proof composite material with a low-temperature curing high-temperature infrared stealth coating on the surface, which is composed of a resin-based heat-proof composite material and a high-temperature infrared stealth coating from the inside to the outside. The resin-based heat-proof composite material uses high-silica fiber as a reinforcement and phenolic resin as a resin matrix. The reinforcement is woven in a needle-punched fabric. The density of the resin-based heat-proof composite material is 0.63g / cm 3 . The high-temperature infrared stealth coating is composed of a low-emissivity filler and a bonding phase. The mass fraction of the low-emissivity filler in the high-temperature infrared stealth coating is 95%, and it is composed of a mixed filler of 80% nano-silver palladium powder and 20% flaky aluminum powder. The mass fraction of nano-silver powder in the nano-silver palladium powder is 85%, and the mass fraction of nano-palladium powder is 15%. The particle size of the nano-silver powder is 70nm, the particle size of the nano-palladium powder is 50nm, and the particle size of the flaky aluminum powder is 35μm. The bonding phase is composed of 95% PbO-B 2 O 3 The glass phase and the mass fraction of 5% acrylic resin are composed of PbO-B 2 O 3 The mass fraction of PbO in the glass phase is 25%, 2 O 3 The mass fraction is 75%, the glass softening point is 350°C, and the thickness of the high-temperature infrared stealth coating is 150μm.
[0039] This embodiment also provides a method for preparing a resin-based heat-resistant composite material with a high-temperature infrared stealth coating on its surface, comprising the following steps: (1) Clean the mold, apply release agent on the mold surface, and complete the mold processing; (2) Assemble the resin-based composite fabric and the mold and perform an air tightness inspection; (3) Using a pressure of 0.4 MPa, a liquid phenolic resin with a viscosity of 40 mPa·s was injected into the closed mold cavity to complete the impregnation of the resin-based composite fabric, and then heated and cured at 90 °C for 32 h. After that, the mold was removed to complete the preparation of the resin-based heat-resistant composite material. (4) Grinding and roughening the coating surface of the resin-based heat-resistant composite material to be coated; (5) The high-temperature infrared stealth coating is applied to the surface of the resin-based heat-resistant composite material by a brush coating process, and then cured at 100°C for 2 h and polished to complete the preparation of the high-temperature infrared stealth coating.
[0040] Wherein, in step (5), the high-temperature infrared stealth coating is prepared by the following method: the glass powder after melting and ball milling is passed through a 200-400 mesh sieve, and then the glass powder, nano silver palladium powder, and flaky aluminum powder are mixed evenly, and finally the acrylic resin and the organic carrier are mixed evenly and ground to obtain the high-temperature infrared stealth coating. The organic carrier in the high-temperature infrared stealth coating is mainly composed of 73% by mass of butyl carbitol, 12% by mass of tributyl citrate, 5% by mass of ethyl cellulose, 4% by mass of Span-85, and 6% by mass of 1,4-butyrolactone. The mass fraction of the organic carrier in the high-temperature infrared stealth coating is 20%.
[0041] The high-temperature infrared stealth coating prepared in this embodiment has good adhesion with the surface of the resin-based heat-resistant composite material. After gluing, the coating has no peeling and is grade 0, and the adhesion is qualified. The resin-based heat-resistant composite material coated with the high-temperature infrared stealth coating on the surface has been subjected to 600℃-10min, 1000℃-10min thermal tests, quartz lamp thermal tests (maximum heat flux 150kW / m 2 , the high-temperature infrared stealth coating is intact after the test time of 600s, without cracking or falling off. The measured 3~5μm normal temperature infrared emissivity of the coating in the original state (before the test), after the 600℃ heat test, after the 1000℃ heat test, and after the quartz lamp test are 0.21, 0.10, 0.12, and 0.12, respectively. The infrared emissivity of the high-temperature infrared stealth coating is significantly reduced after the heat test, indicating that the high-temperature infrared stealth coating prepared on the surface of the resin-based heat-resistant composite material exhibits low emissivity characteristics in a wide temperature range, excellent heat resistance, and strong high-temperature bonding with the substrate.
[0042] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A resin-based heat-resistant composite material with a low-temperature curing high-temperature infrared stealth coating on its surface, characterized in that: From the inside to the outside, it includes a resin-based heat-proof composite material and a high-temperature infrared stealth coating. The high-temperature infrared stealth coating is composed of a low-emissivity filler and a bonding phase. The low-emissivity filler is a mixed filler composed of nano silver powder or nano silver palladium powder and flaky aluminum powder. The bonding phase is composed of a glass phase and an organic resin.
2. The resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating according to claim 1, characterized in that: The mass fraction of the low-emissivity filler in the coating is 80%-95%, the mass fraction of nano-silver or nano-silver palladium powder in the mixed filler is 10%-90%, and the mass fraction of flaky aluminum powder is 10%-90%; the mass fraction of nano-palladium in the nano-silver palladium powder is 5%-30%, and the mass fraction of nano-silver is 70%-95%; the particle size of the nano-silver and nano-palladium is 30nm-150nm, and the particle size of the flaky aluminum powder is 5μm-40μm.
3. The resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating according to claim 1, characterized in that: The mass content of the organic resin in the bonding phase is 5% to 10%, and the mass content of the glass phase is 90% to 95%, and the organic resin is one of epoxy resin, acrylic resin, epoxy-modified silicone resin, and fluororesin; the main component of the glass phase is PbO-B2O3, wherein the mass fraction of PbO is 1% to 30%, the mass fraction of B2O3 is 20% to 80%, and the softening point temperature is 350°C to 400°C.
4. The resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating according to claim 1, characterized in that: The resin-based heat-resistant composite material reinforcement is one of carbon fiber, glass fiber, high-silica fiber, aramid fiber, and quartz fiber; the resin matrix is one of epoxy resin, phenolic resin, benzoxazine resin, aromatic acetylene resin, and silicon aromatic acetylene resin; the braiding form of the reinforcement is one of three-dimensional five-directional fabric, 2.5D fabric, stitched fabric, and needle-punched fabric; the density of the resin-based heat-resistant composite material is 0.5g / cm 3 ~1.5g / cm 3 .
5. The resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating according to claim 1, characterized in that: The high-temperature infrared stealth coating has a thickness of 10 μm to 200 μm.
6. A method for preparing a resin-based heat-resistant composite material with a surface coated with a low-temperature curing high-temperature infrared stealth coating as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Preparation of resin-based heat-resistant composite materials; (2) Grinding and roughening the coating surface of the resin-based heat-resistant composite material to be coated; (3) The high-temperature infrared stealth coating is applied to the surface of the resin-based heat-resistant composite material by brushing or room-temperature spraying, and then subjected to low-temperature curing and polishing. The low-temperature curing process parameters are: temperature of 70°C to 100°C and time of 1h to 2h to obtain a high-temperature infrared stealth coating.
7. The preparation method according to claim 6, characterized in that: The step (1) comprises cleaning the mold, applying a mold release agent on the mold surface, and completing mold processing; assembling the resin-based composite material fabric with the mold and performing an air tightness inspection; injecting liquid resin into the closed mold cavity under pressure to complete the infiltration of the resin-based composite material fabric, and obtaining the resin-based heat-resistant composite material through heating, curing, and demolding.
8. The preparation method according to claim 7, characterized in that: The infiltration pressure is 0.2MPa~1.2MPa; the viscosity of the liquid resin is 20mPa‧s~600mPa‧s; the heating curing temperature is 50℃~280℃, and the curing time is 2h~40h.
9. The preparation method according to claim 6, characterized in that: The high-temperature infrared stealth coating is mainly composed of a low-emissivity filler, a binder and an organic carrier; the binder is composed of glass powder and an organic resin; the high-temperature infrared stealth coating is prepared by the following method: the glass powder after melting, water cooling and ball milling is passed through a 200-400 mesh sieve, and then the glass powder and the low-emissivity filler are mixed evenly with a planetary gravity mixer, and then mixed evenly with the organic resin and the organic carrier, and then ground with a three-roll grinder to obtain the high-temperature infrared stealth coating.
10. The preparation method according to claim 9, characterized in that: The organic carrier is mainly composed of 70% to 80% by mass of butyl carbitol, 8% to 12% by mass of tributyl citrate, 2% to 5% by mass of ethyl cellulose, 2% to 5% by mass of Span-85 and 3% to 6% by mass of 1,4-butyrolactone. The mass fraction of the organic carrier in the high-temperature infrared stealth coating is 5% to 25%.
Citation Information
Patent Citations
Oxide-enhanced-oxide-based composite material coated with high-temperature-resistant low infrared emissivity coating and preparation method of composite material
CN104858434A
Environmental barrier-infrared stealth integrated coating, composite material containing coating and preparation method of composite material
CN110002900A
Resin-based heat-proof composite material with surface coated with high-temperature infrared stealth coating and preparation method thereof
CN112920442A
High-adhesion conductive silver paste for ceramic-based composite material and preparation method of high-adhesion conductive silver paste
CN114155992A
External electrode silver paste for low-temperature sintering LTCC (Low Temperature Co-Fired Ceramic) device and preparation method thereof
CN117524541A
Cited By
Infrared stealth composite coating system compatible with low-lightness visible light camouflage and preparation method thereof
CN120890309A